Percepção sócio, econômico e ambiental no fazer artístico do Folguedo da Comunidade Quilombola Tabacaria, Palmeira dos Índios-Alagoas - Cavalcanti, Daniel Andrade (2025)
The various traditional communities such as quilombos have a wide repertoire of knowledge arising from their history and trajectory. Among them, there is knowledge related to social, economic, environmental activities and cultural manifestations. Therefore, they play an important role in maintaining the cultural diversity of humanity, as well as being responsible for undertaking sustainable development in their different territories, where they influence and are influenced by the environment. This knowledge and relationship with the land makes the quilombola territory a space of life and memory. Remnants of a slavery past, quilombola communities are today protected by laws. In Alagoas, among the populations that gained visibility for their struggle for land ownership, is Quilombo da Tabacaria, located in Palmeira dos Índios, the first to be given title in the state. In the process of struggle, despite the setbacks, Tabacaria kept the legacy of its ancestors alive, having in the reisado, one of its greatest cultural expressions. Reisado is a popular party, danced and sung during the Christmas period. This research was carried out between 2023 and 2024, focusing on the local party group. With this research we seek to understand how the festivities present in the Quilombola Tabacaria Community contribute to The study had a methodological contribution in the qualitative approach of the interventional type with community residents, involved in carrying out the reisado, where they were recruited to participate in the research. As an instrument for collecting and analyzing data, we used a semi-structured questionnaire, divided into three parts, social/economic, environmental and cultural. This research generated three products, a film documentary, an Instagram of Reisado Quilombola Tabacaria and a scientific article. We present partial results of this research through summaries, in the form of banners, presentation of oral work in workshops, at local scientific events. Our perception is that in artistic practice, Reisado Quilombo Tabacaria impacts its community and environment, as well as being impacted by them, as they are organically integrated into its location.